Newman and science - Hodgson, Peter E. (Sapientia, 1999)
John Henry Newman (1801-1890) was one of the outstanding religious thinkers of the nineteenth century, and he foresaw many of the religious troubles of the present century. He laboured incessantly to prepare the Church to face them, and had a dominating influence on the Second Vatican Council. He was born in London, and went to Trinity College, Oxford, for his undergraduate studies. After graduation he was elected a Fellow of Oriel College, took Anglican Orders and was appointed Vicar of the University Church of St. Mary the Virgin. Sunday after Sunday he preached to the university, recalling his hearers back to the beliefs of the early Church. He was a leader of the Oxford Movement that tried to establish a Vía Media between the Church of England and what he then believed to be the decadent Roman Church. Eventually, after intense spiritual struggles, he saw that this was a chimera, that it is the Roman Church that has unbroken continuity with the Church of the Fathers, and that the Church of England is but a man-made national Church. He recognised that he could not remain an Anglican and save his soul, and so was received into what he called the One True Fold in 1845. In so doing, he abandoned the secure and well-endowed life of an Oxford don for the uncertainties and privations of life as a Catholic in Victorian England. In spite of many trials, he never looked back or regretted his conversion, affirming that the Hand of God was most wonderfully over him. Soon after his reception, he was ordained to the priesthood and established the Oratory of St. Philip Neri in Birmingham. There he continued his preaching and writing, largely in obscurity. This was changed when an Anglican vicar, the Rev. Charles Kingsley, accused him of advocating lying. To clear his narre, Newman wrote his Apologia pro Vita Sua, giving the full story of his spiritual journey. This reestablished him in the eyes of his countrymen, and the seal was set on his life's work by his elevation to the cardinalate in 1879...